Utilization of bark extract of Phyllanthus emblica as a sustainable corrosion inhibitor to reinforced concrete infrastructures in aggressive environments - Gautam Madhab; Subedi Dhruba B.; Dhungana Jivan R.; Bhattarai Nootan P.; Bhattarai Jagadeesh (E3S Web of Conferences)
Reinforced concrete (ReC) infrastructures are used widely in construction due to their durability and strength. However, the premature corrosion of reinforced concrete (ReC) infrastructures poses a significant global problem. Sustainable corrosion inhibitors from plant extracts offer a promising solution for mitigating reinforced concrete corrosion (ReCC). This study examines the anti-corrosive effects of bark extract of the Phyllanthus emblica (BEPE) tree as a concrete additive in aggressive environments. Fifteen rectangular ReC beams were exposed in simulated industrial and marine environments and ambient atmospheric conditions using concrete composite (CC) with and without different concentrations of BEPE (500 ppm, 1000 ppm, 2000 ppm, and 4000 ppm). The electrochemical analysis of the reinforced-mild steel (ReMS) rod involved measuring electrochemical corrosion potential (ϕEcor) and electrochemical resistivity (RE), according to ASTM C876-91 standards for seven months. The phytochemical screening, UV-visible, and FT-IR spectroscopic analyses confirmed the presence of secondary metabolites in BEPE, which create a protective layer on the steel surface, reducing corrosion of the ReMS rod. Higher concentrations of BEPE demonstrated better corrosion inhibition in all environments, with shifts of ϕEcor to more positive than -126 mV and RE to more than 20 KΩ.cm value, indicating reduced corrosion of the ReMS rod in CC exposing in three different environments (i.e., normal, industrial and marine). Optical image analysis of the ReMS supported the electrochemical findings. This research could pave the way for developing new, environmentally friendly corrosion inhibitors for concrete additives.